Epidemiološke i kliničke karakteristike Clostridium difficile infekcije prije i tokom COVID-19 pandemije: Epidemiological and clinical characteristics of Clostridium difficile infections - Knežević, Darija; Jović, Duška; Petković, Miroslav (Scripta Medica, 2023)
Background/Aim: Diarrhoea that occurs as a result of the presence of Clostridiumdifficile (reclassified as Clostridoides difficile) is usually manifested as a hospitalinfection, usually after antibiotic treatment. The study aim was to assessthe incidence, characteristics and outcomes of hospitalised patients with healthcare– associated Clostridioides difficile infection ( HA - CDI) before and duringthe COVID-19 pandemic.Methods: This retrospective cohort study included patients older than 18, whomet the HA - CDI case definition. The CDI diagnosis was made by demonstratingtoxins A and B in stool samples using an immunochromatographic assay testand polymerase chain reaction (PCR).Results: The incidence of HA - CDI has significantly decreased from the pre-COVID-19 period to the COVID-19 period (11.04 per 10,000 vs 6.49 per 10,000,p < 0.001). Before establishing the HA - CDI diagnosis, 41.4 % of patients usedone antibiotic, 25.9 % used two and 11.2 % were treated with three or moreantibiotics. Almost one half of the applied antibiotics were from the group thatrepresents high risk for the development of HA - CDI. Multivariable logistic regressionanalysis showed that older age (OR = 3.4; 95 % CI = 0.9-12.4; p = 0.038)and complicated disease course (OR = 11.8; 95 % CI = 2.6-53.6; p ≤ 0.001) wereassociated with a higher risk of death.Conclusion: The incidence of HA - CDI has decreased during the observed periodof the COVID-19 pandemic, however, no clear connection between the impactof the pandemic and incidence reduction was found. Due to unfavourableoutcome of the treatment of HA - CDI patients during COVID-19 pandemic, therational use of antibiotics is necessary.
Keywords: Clostridium difficile infekcije; COVID-19; Faktori rizika; Izbijanje bolesti